PENYADAPAN DALAM TINDAK PIDANA TERORISME DI INDONESIA DAN FILIPINA DITINJAU DARI PERSPEKTIF HAK ASASI MANUSIA - -, Shinta Dewi Kumalasari (Penerbit Universitas Atma Jaya Yogyakarta, 2023)
Terrorism in Indonesia and the Philippines is growing rapidly. Wiretapping is used as a method of investigating terrorists. The purpose of this study is to find out and examine whether wiretapping of terrorism suspects according to the terrorism law is with human rights and the reasons why wiretapping terrorism in Indonesia takes a longer period of time than in the Philippines. Normative research method with statutory approach and comparative law. Sources of data in the form of secondary data consisting of primary legal materials and secondary legal materials. Wiretapping has not been specifically regulated in the law, while in practice it has caused controversy over the wiretapping procedure. Wiretapping is a problem because it violates the privacy rights of citizens. Wiretapping must be carried out in line with human rights principles including technical and licensing so that it can prove that wiretapping is certainly intended to provide protection. Wiretapping in Indonesia takes longer because terrorism networks in Indonesia are not centered on one area, so it takes a relatively long time to conduct wiretapping.